INVESTIGATING THE RELATIONSHIP BETWEEN SELF-EFFICACY AND STUDENTS’ LEARNING SATISFACTION WITH THE ONLINE LEARNING ENVIRONMENT - Nur Syafizan Mohd Sufter; Nora Baizura Mohd Isa; Fazillah Bosli; Mohd Rijal Ilias; Shahida Farhan Zakaria, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Online learning has become important in education because of the changes brought about during the COVID-19 pandemic. The change in the conventional way of face-to-face learning to online learning also affects the satisfaction of learning for students. Therefore, this study aims to determine the relationship between student satisfaction and self-efficacy in online learning, and to examine the self-efficacy factors that most influence online learning satisfaction. A sample of 187 students from Diploma in Computer Science course was selected to complete an online survey questionnaire. The survey used in this study consists of an online learning self-efficacy questionnaire and an electronic learning satisfaction questionnaire. Data was analyzed using SPSS statistical tools. Descriptive statistics, including means and standard deviations, were used to summarize and describe demographic data. In addition, correlation analysis is used to find out the relationship between variables while regression analysis is used to analyze which factors most influence online learning satisfaction. The results show that all three factors show a significant relationship. This means that self-efficacy in learning, time management, and technology play an important role in student satisfaction in online learning. Meanwhile, self-efficacy in learning is the factor that most influences online learning satisfaction.